Need of Today: Creating an Enterprise Wide Social Media Usage Policy - Tomar, Jitendra Singh (Prabandhan: Indian Journal of Management, 2016)
The use of social networking sites is on a high and is increasing with time. Organizations tend to use the platform of social media for various business processes and for a wide range of business activities. Increasingly, companies are ascertaining formulation of guidelines to shun chances of detrimental acts, which could potentially risk the organization due to unacceptable conduct of an employee over social media. This study probed the implementation of social media policies by organizations and the associated benefits which can be brought about by enforcing these policies. Since the popularity and continued growth of social media tools is enormous, their impact on organizational business activities is also large. Organizations should be proactive in creating social media usage policies, if not yet created, with the consent of employees and other involved stakeholders. Furthermore, if policies are in place, organizations should review the policies to incorporate changes occurring due to changes witnessed in the dynamic medium of the Internet and social media. Policy implementation will inform employees about acceptable and unacceptable conduct, and they will be aware of social media usage expectations of the organization. This will check social media usage by employees and will cut down the associated risks for employees and organizations.